Center-Pivot-Irrigated Corn Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1998)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated corn production in Kansas.
MF585_1998_10
Keywords: MF585; Economics; Crops; MF